Impact of voriconazole plasma concentrations on treatment response in critically ill patients. (9th March 2019) - Ruiz, Jesus; Gordon, Mónica; Villarreal, Esther; Peruccioni, Marcela; Marqués, María Remedios; Poveda‐Andrés, Jose Luis; Castellanos‐Ortega, Álvaro; Ramirez, Paula
Summary: What is known and objective: Several authors have demonstrated the relationship between voriconazole concentrations and the risk of therapeutic failure and adverse events However, the information about voriconazole concentrations in the critically ill patient is scarce. The aim of this study was to analyse the plasma concentrations and pharmacokinetic behaviour of voriconazole in critically ill patients and their association with the treatment response and development of toxicity. Methods: A prospective, observational study was conducted. Patients admitted to an intensive care unit and on treatment with intravenous voriconazole were included. Plasma concentrations were measured between days 4 and 7 from the start of the treatment. The pharmacokinetic analysis was performed using the NONMEM ® software. A regression model was used to evaluate the variables associated with the values outside the therapeutic range, as well as the relationship between the plasma concentrations and the treatment response and the development of hepatotoxicity. Results and discussion: A total of 33 patients were included. Plasma concentrations outside the therapeutic range (1‐5.5 mg/L) were observed in 15 patients, being above the established range in 9 (27.3%) cases, and below it in 6 (18.2%) cases. The presence of a bilirubin value of >1.5 mg/dL and a C‐reactive protein >100 mg/dL was associated with supra‐therapeutic concentrations. Voriconazole concentrations greater than 5.5 mg/dL were associated with the development of hepatotoxicity. What is new and conclusions: There is a wide variation in voriconazole concentrations in critically ill patients, being associated with a high frequency of adverse events. Close monitoring of these values is required in order to decrease the risk of therapeutic failure and toxicity. Abstract : The administration of intravenous voriconazole in critically ill patients is associated with a wide variability of concentrations. Bilirubin and C‐Reactive protein are associated with high concentrations of voriconazole, and, therefore, at the risk of toxicity.